Zastosowanie autologicznej surowicy krwi w leczeniu chorób powierzchni oka - Wilczyński, Michał (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
In the literature, there is evidence suggesting that autologous serum eyedrops can be helpful in the treating various ocular conditions. Using eyedrops containing the 20-100% solution of patient’s own serum, centrifuged 3000-4000 rpm, diluted in either saline, BSS or chloramphenicol solution, is a relatively new therapeutic strategy. Nevertheless, in some publications, a positive influence of using autologous serum topically has been proven in numerous ocular diseases. It has been found, that using autologous serum eyedrops is safe, such eyedrops can be stored in temperature ranging from -30°C to +4°C. Moreover, effectiveness of this treatment has been proven for many diseases, e.g.: keratoconjunctivitis sicca, superior limbal keratoconjunctivitis, recurrent erosion syndrome and persistent epithelial defects. Although, complications of the treatment are possible, according to available data from the literature, they are not frequent. A unified standard of preparing the autologous serum eyedrops has not been elaborated and in various publications different modes of preparation of the solution have been used. It is important to document indications for this treatment appropriately, as well as to be cautious while preparing and using the solution.